2016
DOI: 10.1097/01.aoa.0000482638.95936.d7
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Echocardiographic Assessment of Haemodynamics in Severe Preeclampsia and HIV in South Africa

Abstract: (Anaesthesia. 2015, 70, 1028–1038) Preeclampsia and human immunodeficiency virus (HIV) infection are 2 serious global health problems for women. Although preeclampsia affects 6.5 million women each year, HIV infection affects 1.5 million pregnant women globally, with thousands of maternal deaths complicated by HIV infection. In South Africa, both are significant health problems. The objectives of this study were: to determine hemodynamics using transthoracic echocardiography (TTE) in women with preec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After controlling for traditional vascular and sex-specific stroke risk factors, women living with HIV had a statistically significant hazard ratio of 1.89 (95% CI 1.28-2.81) compared to women without HIV (Chow et al, 2018). A study using transthoracic echocardiography in women with HIV at term found reduced left and right ventricular systolic function and increased ventricular dilation compared to HIVnegative controls in South Africa (Dennis et al, 2015). These data suggest that pregnant women with HIV may have increased risk of stroke, but more research is needed.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…After controlling for traditional vascular and sex-specific stroke risk factors, women living with HIV had a statistically significant hazard ratio of 1.89 (95% CI 1.28-2.81) compared to women without HIV (Chow et al, 2018). A study using transthoracic echocardiography in women with HIV at term found reduced left and right ventricular systolic function and increased ventricular dilation compared to HIVnegative controls in South Africa (Dennis et al, 2015). These data suggest that pregnant women with HIV may have increased risk of stroke, but more research is needed.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%